Analisis Pengaruh Transaction Cost terhadap Holding Period Saham Biasa (Studi Kasus pada Bursa Efek Jakarta Tahun 2000) - Subali Subali; Diana Zuhroh (The Indonesian Journal of Accounting Research, 2013)
The ideas of this study arises from the differences result between Atkin's study (1997) and Leny's study (1999). Both of them investigate the relationship between transaction cost and holding period common stock for long term period. The different results are posibly caused by the difference condition of the capital market.  Leny's  study used Jakarta Stock Exchange and Atkin's study used New York Stock Exchange and Nasdaq. The real condition of the Jakarta Stock Exchange is most of the investors prefer to capital gain oriented from buy and sell transaction than devidend for the end of the year. So it’s more adaptable if we use short term to investigate  the relationship transaction cost and holding period.The statistical method used in this study is two-stage least square regression.The statistical result shows that bid-ask spread related positively and significant of the holding period. The bid-ask spread, market value, and risk of return can be used for predicting the variations of holding period.